Health technology literacy a transdisciplinary framework for consumer-oriented practice - Jordan-Marsh, Maryalice; Immroth, Barbara Froling (Jones & Bartlett Learning, 2011)
Telehealth as a fulcrum in health technology -- Literacy for an age of eHealth -- Health information seeking behavior on the Web -- The personal health record building human capital for health -- Devices as adjuncts to being healthy at home -- Digital games : consumer resources for health capital -- Consumer-centric health technology : wicked problems and deliciously disruptive solutions